PERENCANAAN CHECK DAM DAS LUSI DI KABUPATEN BLORA - Septina Qurniawati; Ivanna Susanto; Pranoto Samto Admodjo; Sri Sangkawati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The unequal streamflow in Lusi Watershed throughout the year is caused by the disrupted hydrological cycle. Excess water during the rainy season that will be wasted and cause flood. Otherwise water scarcity happens during the dry season that cause drought.Besides there are many meandering that cause scour in river bend and landslide that may affect in the amount of sediment accumulated in Lusi riverbank. To address these issues, creating shortcut and building check dam are one of the approriate alternate ways. This shortcut is to overcome the landslide that is located near the village road. Otherwise the building of this check dam is to overcome the scour and landslide that cause sedimentation. In addition it is aimed to decelerate the velocity of water flowing in Lusi riverbank and also will be modified as a storage in old riverduring the dry season. The calculation of the design flood discharge is to determine the maximum discharge of the river with a certain return period using Rational, Haspers, FSR Jawa-Sumatra and Passing Capacity Method. According to the analysis result, the design flood discharge is 786.3 m3/s and the erosion and sedimentation level is 56.039 tons/ha/year estimated by USLE Method. From the calculation the height of check dam is 4 m, it collects water 326938 m3, that will be benificial for the people in dry season.